Role of ARPC2 in Human Gastric Cancer. (13th June 2017) - Zhang, Jun; Liu, Yi; Yu, Chang-Jun; Dai, Fu; Xiong, Jie; Li, Hong-Jun; Wu, Zheng-Sheng; Ding, Rui; Wang, Hong
Abstract : Gastric cancer continues to be the second most frequent cause of cancer deaths worldwide. However, the exact molecular mechanisms are still unclear. Further research to find potential targets for therapy is critical and urgent. In this study, we found that ARPC2 promoted cell proliferation and invasion in the human cancer cell line MKN-28 using a cell total number assay, MTT (3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2-H-tetrazolium bromide) assay, cell colony formation assay, migration assay, invasion assay, and wound healing assay. For downstream pathways, CTNND1, EZH2, BCL2L2, CDH2, VIM, and EGFR were upregulated by ARPC2, whereas PTEN, BAK, and CDH1 were downregulated by ARPC2. In a clinical study, we examined the expression of ARPC2 in 110 cases of normal human gastric tissues and 110 cases of human gastric cancer tissues. ARPC2 showed higher expression in gastric cancer tissues than in normal gastric tissues. In the association analysis of 110 gastric cancer tissues, ARPC2 showed significant associations with large tumor size, lymph node invasion, and high tumor stage. In addition, ARPC2-positive patients exhibited lower RFS and OS rates compared with ARPC2-negative patients. We thus identify that ARPC2 plays an aneretic role in human gastric cancer and provided a new target for gastric cancer therapy.